Preparation method and application of h-MOF@E immobilized enzyme reactor
By constructing h-MOF nanospheres with single-open hollow morphology, an immobilized enzyme reactor was prepared, which solved the problems of insufficient enzyme loading and poor catalytic performance in traditional immobilized enzyme technology, and achieved efficient enzyme catalysis and good reuse performance.
Patent Information
- Application Number
- CN202411940796.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
AI Technical Summary
Traditional immobilized enzyme technology has problems with insufficient enzyme loading and poor catalytic performance, especially in terms of the matching of enzymes to carriers and mass transfer resistance.
H-MOF nanospheres with single-open hollow morphology were constructed by a one-pot solvent-heat reaction method. They were formed by cross-assembly of ultra-thin nanosheets with a thickness of 1 to 2 nm. The specific surface area is large and contains large irregular breakage. They were used to prepare an h-MOF@E immobilized enzyme reactor.
It improves the solid loading of the enzyme, avoids physical extrusion of the active enzyme, enhances the catalytic activity and reuse performance of the enzyme, and has potential commercial value.
Smart Images

Figure CN119736286A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of immobilized enzymes, and in particular to a preparation method and application of an h-MOF@E immobilized enzyme reactor. Background Art
[0002] Bioactive peptides (BAP) are polypeptide compounds widely found in animals and plants. Due to the structural diversity of its unique amino acid composition and rich hydrophobic residues, BAP has multiple biological activities such as antioxidant, anti-aging and anti-cancer, but the content of BAP in animal and plant extracts is extremely low. Therefore, the synthesis of BAP has received widespread attention. The preparation methods of BAP include direct extraction, chemical synthesis and microbial fermentation. However, the above methods have high equipment requirements, low efficiency and are not environmentally friendly. In contrast, the enzyme-catalyzed synthesis of BAP is green and efficient, and is an effective way to achieve industrial production of BAP.
[0003] my country is rich in snake resources, but a large amount of scraps are produced during the processing. If not effectively treated, it will not only pollute the environment, but also cause serious waste of resources. Snake skin is rich in collagen. Currently, the use of enzymes to synthesize BAP from animal and plant skins has a wide range of applications, spanning the food, medicine, cosmetics and other industries. It can be seen that the synthesis of BAP using snake skin as raw material has a good prospect.
[0004] Compared with free enzyme catalysis, immobilized enzyme technology can significantly improve the stability and recycling performance of enzymes, and is of great significance in the continuous production of biosynthesis, energy saving, and environmental protection. However, there are two prominent problems with traditional immobilization technology: First, if the enzyme is fixed on a large-sized carrier without pores, it often leads to surface loading, which cannot well protect the enzyme molecules, easily leading to leakage and affecting the catalytic efficiency; and restricting the enzyme to a small and narrow channel may cause physical extrusion or affect the enzyme's freedom as a flexible molecule and affect its efficiency; second, the mass transfer resistance caused by the intervention of the carrier is another major challenge of immobilization. The enzyme tightly fixed inside the carrier is difficult to interact with the substrate, which reduces the overall catalytic activity, which is particularly unfavorable for some multi-enzyme synergistic reactions. Therefore, in order to synthesize BAP by enzyme catalysis, it is necessary to develop an efficient immobilized enzyme carrier material.
[0005] Metal-organic frameworks (MOFs) materials have the advantages of large specific surface area, adjustable pore size and morphology, and high thermal stability, making them excellent carriers for immobilized enzymes. Traditional MOFs immobilization methods include physical adsorption, covalent grafting, and embedding. However, the mismatch between the pore size of traditional MOFs and the size of the enzyme will lead to insufficient enzyme loading and easy detachment during the catalytic process. The use of coupling agents or in-situ MOFs embedding will lead to insufficient space for the enzyme, affecting the catalytic efficiency. In recent years, great progress has been made in the nanoengineering and morphology control of MOFs materials. If a hollow nano-MOFs material with certain defects can be synthesized through morphology control, it will have far-reaching significance for the construction of a new type of immobilized enzyme reactor.
[0006] Based on this, the present invention is proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a preparation method and application of an h-MOF@E immobilized enzyme reactor to solve the problems of insufficient loading and poor catalytic performance in the conventional enzyme immobilization method in the prior art.
[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0009] The present invention provides a method for preparing an h-MOF@E immobilized enzyme reactor, comprising the following steps:
[0010] (1) mixing terephthalic acid, N,N-dimethylacetamide and isopropyl alcohol to obtain a mixed solution A;
[0011] (2) mixing nickel acetate tetrahydrate, zinc acetate dihydrate, N,N-dimethylacetamide and isopropanol to obtain a mixed solution B;
[0012] (3) mixing the mixed solution A with the mixed solution B, heating for 2 to 4 hours, centrifuging, washing, and drying to obtain h-MOF nanospheres;
[0013] (4) mixing the h-MOF nanospheres with the active protease solution, shaking for 2 to 4 hours, centrifuging, washing, and drying to obtain the h-MOF@E immobilized enzyme reactor;
[0014] The mass volume ratio of terephthalic acid and N,N-dimethylacetamide in step (1) is 16-20 mg: 6-8 mL;
[0015] The mass volume ratio of the terephthalic acid and isopropyl alcohol is 16-20 mg: 3-5 mL.
[0016] Preferably, the mass ratio of nickel acetate tetrahydrate to zinc acetate dihydrate in step (2) is 48-50:21-22;
[0017] The mass volume ratio of the nickel acetate tetrahydrate and N,N-dimethylacetamide is 48-50 mg: 6-8 mL;
[0018] The mass volume ratio of the nickel acetate tetrahydrate and isopropanol is 48-50 mg:3-5 mL.
[0019] Preferably, in step (3), the volume ratio of the mixed solution A to the mixed solution B is 1-2:1-2.
[0020] Preferably, the heating temperature in step (3) is 140-160°C.
[0021] Preferably, in step (4), the mass volume ratio of the h-MOF nanospheres and the active protease solution is 1-2 mg: 1-2 mL.
[0022] Preferably, the active protease in step (4) is trypsin, papain, pepsin or flavor protease;
[0023] The initial concentration of the active protease solution is 0.5-1.5 mg / mL.
[0024] Preferably, the oscillation speed in step (4) is 100 to 200 rpm.
[0025] The present invention provides an h-MOF@E immobilized enzyme reactor obtained by the preparation method, wherein the structure of the h-MOF@E immobilized enzyme reactor is a single-opening hollow sphere.
[0026] The present invention also provides the use of the h-MOF@E immobilized enzyme reactor obtained by the preparation method in the preparation of antioxidant, anti-aging or anti-cancer products.
[0027] The present invention has the following technical effects and advantages:
[0028] The present invention constructs h-MOF nanospheres with a single-opening hollow morphology through a one-pot solvothermal reaction method. The nanospheres are formed by cross-assembly of ultrathin nanosheets with a thickness of 1 to 2 nm, have a large specific surface area, and also contain a large irregular break with a pore size of about 100 to 500 nm. The large specific surface area and irregular break structure are conducive to increasing the enzyme immobilization capacity. At the same time, the large internal cavity will not form physical extrusion on the active enzyme, affect the enzyme as a flexible molecule, and affect its performance. Using h-MOF nanospheres as carriers, a novel single-opening hollow spherical h-MOF@E immobilized enzyme reactor can be prepared through a simple immobilization technology. The obtained h-MOF@E immobilized enzyme reactor has excellent snakeskin collagen catalytic activity and reusability, and has potential commercial value. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 SEM images of h-MOF nanospheres and s-MOF nanospheres;
[0030] Figure 2 N2 adsorption-desorption isotherm curves of h-MOF nanospheres and s-MOF nanospheres;
[0031] Figure 3 The structures and elemental characterization diagrams of h-MOF nanospheres, h-MOF@E1, and h-MOF@E2;
[0032] Figure 4 X-ray diffraction patterns and infrared spectra of h-MOF nanospheres, s-MOF nanospheres h-MOF@E1 and h-MOF@E2;
[0033] Figure 5 The hydrolysis degree and DPPH free radical scavenging rate of the enzymatic hydrolysate of the reactor with different immobilized enzymes added;
[0034] Figure 6 The effects of different h-MOF@E1 addition amounts, pH values, temperatures and enzymatic hydrolysis times on the activity of the immobilized enzyme;
[0035] Figure 7 The effect of different cycle numbers of h-MOF@E1 reactor on the enzymatic efficiency of immobilized enzyme. DETAILED DESCRIPTION
[0036] The present invention provides a method for preparing an h-MOF@E immobilized enzyme reactor, comprising the following steps:
[0037] (1) mixing terephthalic acid, N,N-dimethylacetamide and isopropyl alcohol to obtain a mixed solution A;
[0038] (2) mixing nickel acetate tetrahydrate, zinc acetate dihydrate, N,N-dimethylacetamide and isopropanol to obtain a mixed solution B;
[0039] (3) mixing the mixed solution A with the mixed solution B, heating for 2 to 4 hours, preferably for 3 hours, centrifuging, washing, and drying to obtain h-MOF nanospheres;
[0040] (4) mixing the h-MOF nanospheres with the active protease solution, shaking for 2 to 4 hours, preferably for 3 hours, centrifuging, washing, and drying to obtain the h-MOF@E immobilized enzyme reactor;
[0041] The mass volume ratio of terephthalic acid and N,N-dimethylacetamide in step (1) is 16-20 mg: 6-8 mL, preferably 16-18 mg: 7-8 mL, and more preferably 16.6 mg: 7.5 mL;
[0042] The mass volume ratio of terephthalic acid and isopropyl alcohol is 16-20 mg: 3-5 mL, preferably 16-18 mg: 4-5 mL, and more preferably 16.6 mg: 4.5 mL.
[0043] In the present invention, the mass ratio of nickel acetate tetrahydrate to zinc acetate dihydrate in step (2) is 48-50:21-22, preferably 49-50:21-22, and more preferably 49.7:21.9;
[0044] The mass volume ratio of nickel acetate tetrahydrate to N,N-dimethylacetamide is 48-50 mg:6-8 mL, preferably 49-50 mg:7-8 mL, and more preferably 49.7 mg:7.5 mL;
[0045] The mass volume ratio of the nickel acetate tetrahydrate to isopropanol is 48-50 mg:3-5 mL, preferably 49-50 mg:4-5 mL, and more preferably 49.7 mg:4.5 mL.
[0046] In the present invention, the volume ratio of the mixed solution A to the mixed solution B in step (3) is 1-2:1-2, preferably 1:1.
[0047] In the present invention, the heating temperature in step (3) is 140-160°C, preferably 150°C.
[0048] In the present invention, the mass volume ratio of the h-MOF nanospheres and the active protease solution mixed in step (4) is 1-2 mg: 1-2 mL, preferably 1 mg: 1 mL.
[0049] In the present invention, the active protease in step (4) is trypsin, papain, pepsin or flavor protease;
[0050] The initial concentration of the active protease solution is 0.5-1.5 mg / mL, preferably 1 mg / mL;
[0051] The solvent for dissolving the active protease solution is a phosphate buffer solution at pH=7.
[0052] In the present invention, the oscillation rate in step (4) is 100-200 rpm, preferably 150 rpm.
[0053] The present invention provides an h-MOF@E immobilized enzyme reactor obtained by the preparation method, wherein the structure of the h-MOF@E immobilized enzyme reactor is a single-opening hollow sphere.
[0054] The present invention also provides the use of the h-MOF@E immobilized enzyme reactor obtained by the preparation method in the preparation of antioxidant, anti-aging or anti-cancer products.
[0055] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0056] In the examples of the present invention, trypsin, papain, pepsin and flavor protease were purchased from Nanjing Dongheng Huadao Biotechnology Co., Ltd., wherein E1 represents trypsin, E2 represents papain, E3 represents pepsin, and E4 represents flavor protease.
[0057] Example 1
[0058] (1) 7.5 mL of N,N-dimethylacetamide and 4.5 mL of isopropanol were mixed to obtain a mixed solution, and then 16.6 mg of terephthalic acid was added and mixed to obtain a mixed solution A;
[0059] (2) 7.5 mL of N,N-dimethylacetamide and 4.5 mL of isopropanol were mixed to obtain a mixed solution, and then 49.7 mg of nickel acetate tetrahydrate and 21.9 mg of zinc acetate dihydrate were added and mixed to obtain a mixed solution B;
[0060] (3) 12 mL of mixed solution B was slowly added dropwise to 12 mL of mixed solution A, stirred evenly, and then added into a stainless steel autoclave, heated at 150 ° C for 3 h, and the obtained product was centrifuged, washed, and dried to obtain h-MOF nanospheres;
[0061] (4) A trypsin solution with a concentration of 1.0 mg / mL was prepared using a phosphate buffer solution with a pH of 7.0. 25 mg of h-MOF nanospheres were weighed and dispersed in 25 mL of the trypsin solution. The mixture was shaken at a speed of 150 rpm for 3 h, and then centrifuged, washed, and dried to obtain a reactor h-MOF@E1 for immobilizing trypsin.
[0062] Example 2
[0063] The preparation method is the same as that of Example 1, except that the protease solution used in (4) is a papain solution with a concentration of 1.0 mg / mL, and a reactor h-MOF@E2 with immobilized papain is obtained.
[0064] Example 3
[0065] The preparation method is the same as that in Example 1, except that the protease solution used in (4) is a pepsin solution with a concentration of 1.0 mg / mL, and a reactor h-MOF@E3 with immobilized pepsin is obtained.
[0066] Example 4
[0067] The preparation method is the same as that of Example 1, except that the protease solution used in (4) is a flavor protease solution with a concentration of 1.0 mg / mL, and a reactor h-MOF@E4 with immobilized flavor protease is obtained.
[0068] Comparative Example 1
[0069] (1) Dissolve 16.6 mg of terephthalic acid in 12 mL of N,N-dimethylacetamide and mix well to obtain a mixed solution A;
[0070] (2) dissolving 49.7 mg of nickel acetate tetrahydrate and 21.9 mg of zinc acetate dihydrate in 12 mL of N,N-dimethylacetamide, and mixing them uniformly to obtain a mixed solution B;
[0071] (3) 12 mL of mixed solution B was slowly added dropwise to 12 mL of mixed solution A, stirred evenly, and then added into a stainless steel autoclave, heated at 150 ° C for 3 h, and the obtained product was centrifuged, washed, and dried to obtain s-MOF nanospheres;
[0072] (4) A trypsin solution with a concentration of 1.0 mg / mL was prepared using a phosphate buffer solution with a pH of 7.0. 25 mg of s-MOF nanospheres were weighed and dispersed in 25 mL of the trypsin solution. The mixture was shaken at a speed of 150 rpm for 3 h, and then centrifuged, washed, and dried to obtain a reactor s-MOF@E1 for immobilized trypsin.
[0073] Comparative Example 2
[0074] The preparation method is the same as that of Comparative Example 1, except that the protease solution used in (4) is a papain solution with a concentration of 1.0 mg / mL, and a reactor s-MOF@E2 for immobilizing papain is obtained.
[0075] Comparative Example 3
[0076] The preparation method is the same as that of Comparative Example 1, except that the protease solution used in (4) is a pepsin solution with a concentration of 1.0 mg / mL, and a reactor s-MOF@E3 for immobilizing pepsin is obtained.
[0077] Comparative Example 4
[0078] The preparation method is the same as that of Comparative Example 1, except that the protease solution used in (4) is a flavor protease solution with a concentration of 1.0 mg / mL, and a reactor s-MOF@E4 for immobilizing flavor protease is obtained.
[0079] Experimental Example 1: Structural Characterization of Different Immobilized Enzyme Carrier Nanospheres and Immobilized Enzyme Reactors
[0080] (1) Structural characterization of immobilized enzyme carrier nanospheres
[0081] The h-MOF nanospheres and s-MOF nanospheres in Example 1 and Comparative Example 1 were observed using a scanning electron microscope (SEM). The SEM images of the h-MOF nanospheres and s-MOF nanospheres are shown in FIG. Figure 1 As shown, in the figure a is the SEM image of s-MOF nanospheres at 500nm, b is the SEM image of s-MOF nanospheres at 200nm, c is the SEM image of h-MOF nanospheres at 500nm, and d is the SEM image of h-MOF nanospheres at 200nm.
[0082] according to Figure 1 It can be observed that the s-MOF nanospheres synthesized under traditional solvothermal conditions present mesoporous solid sphere morphology with different particle sizes, with a particle size distribution of 400-980nm, and the h-MOF nanospheres have a hollow nanosphere morphology with a diameter of 1-2μm, which is formed by the cross-assembly of smaller nanosheets, with a thickness of about 1-2nm, and most of the h-MOF nanospheres are incomplete, with a single irregular pore with a pore size of 100-500nm. This shows that isopropanol can promote the growth of h-MOF nanospheres in a specific direction during the solvothermal reaction, and the mixed solvent formed by isopropanol and N,N-dimethylacetamide limits the further growth of h-MOF nanospheres and forms breaks in local areas, thus obtaining a single open-hole hollow sphere morphology of cross-assembly of nanosheets.
[0083] The surface areas of the h-MOF nanospheres and s-MOF nanospheres in Example 1 and Comparative Example 1 were measured using N2 adsorption-desorption isotherms. The N2 adsorption-desorption isotherms of the h-MOF nanospheres and s-MOF nanospheres are shown in FIG. Figure 2 As shown in the figure, the horizontal axis represents the relative partial pressure (P / P°) and the vertical axis represents the volume (cm 3 (STP) -1 ), the red solid five-pointed star represents the adsorption curve of h-MOF nanospheres, the hollow five-pointed star represents the desorption curve of h-MOF nanospheres, the black solid inverted triangle represents the adsorption curve of s-MOF nanospheres, and the hollow inverted triangle represents the adsorption curve of s-MOF nanospheres.
[0084] according to Figure 2 It can be seen that the specific surface areas of s-MOF nanospheres and h-MOF nanospheres are 162.9784 m 2 g -1 and 393.8422m 2 g-1 Compared with the mesoporous s-MOF solid sphere carrier, the specific surface area of the single-opening hollow spherical h-MOF is significantly improved.
[0085] (2) Structural characterization of immobilized enzyme reactor
[0086] The microstructures of the h-MOF nanospheres, h-MOF@E1 and h-MOF@E2 in Example 1 and Example 2 were characterized by a projection electron microscope (TEM), and the elemental compositions of the h-MOF nanospheres, h-MOF@E1 and h-MOF@E2 in Example 1 and Example 2 were characterized by an energy dispersive X-ray spectrometer (EDS). The structures and elemental characterization diagrams of the h-MOF nanospheres, h-MOF@E1 and h-MOF@E2 are shown in FIG. Figure 3 As shown in the figure, a is the TEM image of h-MOF nanospheres at 500nm, b is the TEM image of h-MOF nanospheres at 200nm, c is the EDS image of h-MOF nanospheres at 500nm and other elements, d is the TEM image of h-MOF@E1 at 500nm, e is the TEM image of h-MOF@E1 at 200nm, f is the EDS image of h-MOF@E1 at 500nm and elements, g is the TEM image of h-MOF@E2 at 500nm, h is the TEM image of h-MOF@E2 at 200nm, and i is the EDS image of C, O, Ni, Zn and S elements of h-MOF@E2 at 500nm.
[0087] according to Figure 3 It can be seen that the h-MOF nanospheres present a typical hollow spherical morphology, ultra-thin nanosheets are evenly distributed on the surface of the spheres, the pores of the spheres are clearly visible, and EDS detection shows that elements such as C, O, Ni and Zn are evenly distributed on the surface of the spheres; when trypsin is compounded with h-MOF, h-MOF@E1 still maintains the original morphology of the carrier, but the inner and outer edges of h-MOF@E1 become rough, and the contrast of the internal cavity becomes low. EDS detects that in addition to elements such as C, O, Ni, and Zn, there is also P on its surface. The P element is evenly distributed on the surface and internal cavity of the carrier, indicating that trypsin can successfully enter the internal cavity of the carrier through the pores on the surface of the carrier; similar to h-MOF@E1, h-MOF@E2 after papain is compounded with h-MOF does not change the morphology of the carrier, and the evenly distributed S element detected by EDS can be attributed to the successful immobilization of papain.
[0088] The phase analysis of the h-MOF nanospheres of Example 1, h-MOF@E1, h-MOF@E2 of Example 2 and s-MOF nanospheres of Comparative Example 1 was performed using an X-ray diffractometer. The results are as follows: Figure 4As shown in a, the horizontal axis represents the diffraction angle 2θ (degree) and the vertical axis represents the intensity (au).
[0089] according to Figure 4 It can be seen from a that the prepared s-MOF nanospheres and h-MOF nanospheres have similar diffraction peaks, indicating that they have consistent topological structures. The diffraction peak intensities of s-MOF and h-MOF at 2θ=6.8° and 8.9° are different, which may be caused by the different exposed crystal faces of different materials. The diffraction peaks of h-MOF@E1 and h-MOF@E2 and h-MOF nanospheres are basically consistent, indicating that the immobilization of the enzyme did not change the topological structure of the carrier.
[0090] The structures of the h-MOF nanospheres of Example 1, h-MOF@E1, h-MOF@E2 of Example 2 and s-MOF nanospheres of Comparative Example 1 were analyzed by Fourier transform infrared spectrometer. The infrared spectra are shown in FIG. Figure 4 b, the horizontal axis represents the wave number (cm -1 ), the ordinate represents transmittance (%).
[0091] according to Figure 4 b shows that h-MOF nanospheres and s-MOF nanospheres have a wavelength of 3450 cm -1 There is an obvious absorption peak at 3450cm, which is due to the OH stretching vibration of the terephthalic acid ligand. -1 The absorption peak at 1100 cm-1 of h-MOF@E1 is significantly different from that of h-MOF nanospheres, which may be due to the combined effect of the OH stretching vibration of the terephthalic acid ligand and the NH stretching vibration of the amino group of the immobilized enzyme. -1 The absorption peaks at 1600 cm-1 and h-MOF@E2 -1 The absorption peaks at can be attributed to the CP stretching vibration of trypsin and the C=S stretching vibration of papain, respectively. The results show that h-MOF nanospheres successfully loaded different types of enzymes.
[0092] Test Example 2: Catalytic performance test
[0093] (1) Preparation of snake skin collagen
[0094] Cut 1000g of black-necked snake skin into sections, soak it in a 4% NaCl solution for 4 hours, then replace it with a new NaCl solution, repeat 4 times, and drain it; soak it in a 10% NaCO3 solution with stirring for 16 hours, and then wash it with pure water 3 times; freeze-dry the snake skin with a vacuum freeze dryer, and grind it with a grinder to obtain 1000g of snake skin powder; add 10L of n-hexane to degrease the snake skin powder, assist with ultrasound for 2 hours at a frequency of 100KHz, then stir for 12 hours, drain the n-hexane to obtain the defatted snake skin powder; dissolve the defatted snake skin powder in 10L of 1M citric acid solution, let it stand at 4℃ for 40min, then continue to add 50L of 1M citric acid solution, and extract it in a high-pressure steam sterilizer at 105℃ for 1h; after extraction, use a tubular centrifuge The mixture was centrifuged at 30 Hz for 4 times, the snake skin residue was discarded, and the permeate was collected as a crude collagen solution; NaCl was added to the crude collagen solution to a final concentration of 5 M, and the solution was allowed to stand for 24 hours after stirring to completely dissolve the NaCl; the mixture was centrifuged at 30 Hz for 4 times using a tubular centrifuge, and the centrifugal speed was 18000 rpm, and the protein precipitate on the filter cloth was collected; water was added to the protein precipitate, and the protein precipitate was redissolved in a 65°C water bath, the ratio of added water to the protein precipitate was 60 mL:1 g, and the solution was then ultrafiltered with a 10 KDa ultrafiltration membrane for desalting, and the concentrated solution was collected; the collagen concentrated solution was vacuum freeze-dried to obtain snake skin collagen freeze-dried powder, and then a snake skin collagen solution with a concentration of 5 mg / mL was prepared with a PBS solution with a concentration of 0.02 M for later use.
[0095] (2) Screening of immobilized enzyme reactors
[0096] The method for determining the degree of hydrolysis is the o-phthalaldehyde method, specifically, 200 mg of o-phthalaldehyde is dissolved in 5 mL of anhydrous ethanol, 0.5 mL of β-mercaptoethanol, 12.5 mL of 10% SDS solution and 125 mL of 0.1 M sodium borate solution are added respectively, and the volume is fixed to 250 mL, which is recorded as OPA reagent; 50 μL of snake skin collagenase hydrolysate is mixed with 3 mL of OPA reagent, and allowed to stand at room temperature for 10 minutes, and its absorbance is measured at a wavelength of 340 nm, which is recorded as A 样品 , 50 μL of deionized water was mixed with 3 mL of OPA reagent, and the mixture was allowed to stand at room temperature for 10 minutes. The absorbance was measured at a wavelength of 340 nm and recorded as A 空白 , 50 μL of serine standard solution was mixed with 3 mL of OPA reagent, and allowed to stand at room temperature for 10 minutes. The absorbance was measured at a wavelength of 340 nm and recorded as A 标准 , calculate the degree of hydrolysis, the calculation formula of the degree of hydrolysis is as follows:
[0097]
[0098]
[0099] In the calculation formula, C serineNH2 represents the concentration of serine standard solution; C represents the protein concentration in snake skin collagenase hydrolysate; H hot is the total number of peptide bonds contained in collagen (11.1 mmol / g), α=0.8, β=0.5.
[0100] Determination method of DPPH free radical scavenging rate:
[0101] Weigh an appropriate amount of DPPH, prepare a 0.2M DPPH solution, and store it in a brown bottle in the dark and at low temperature. Take a test tube and add 2mL of sample solution, then add 2mL of 0.2M DPPH solution and 2mL of 95% ethanol solution, mix well, let stand at room temperature in the dark for 45 minutes, and measure the absorbance at 517nm. The absorbance value of the sample plus DPPH solution is recorded as A1, and the absorbance value of the sample plus 95% ethanol solution is recorded as A2. Take a test tube and add 2mL of 0.2M DPPH solution and then add 2mL of 95% ethanol solution, mix well, let stand at room temperature in the dark for 45 minutes, and measure the absorbance at 517nm. The absorbance value is recorded as A3. Finally, calculate the DPPH free radical scavenging rate. The calculation formula of DPPH free radical scavenging rate is as follows:
[0102]
[0103] Accurately weigh 25 mL of the snake skin collagen solution obtained in (1), and add 3 mg of h-MOF@E1, h-MOF@E2, h-MOF@E3, h-MOF@E4 of Examples 1 to 4 and s-MOF@E1, s-MOF@E2, s-MOF@E3, s-MOF@E4 of Comparative Examples 1 to 4 to obtain reaction solutions of different immobilized enzyme reactors. The pH of the reaction solution was adjusted to 7.0, and then heated to 50° C. with a constant temperature magnetic stirrer. The enzymatic hydrolysis reaction was carried out for 3 h, and the hydrolysis degree and DPPH free radical scavenging rate of the enzymatic hydrolyzates of the different immobilized enzyme reactors were measured. The results are as follows: Figure 5 As shown, Figure a shows the degree of hydrolysis of the enzymatic hydrolysate after adding different immobilized enzyme reactors, wherein the abscissa represents the immobilized enzyme reactor and the ordinate represents the degree of hydrolysis (%); Figure b shows the DPPH radical scavenging rate of the enzymatic hydrolysate after adding different immobilized enzyme reactors, wherein the abscissa represents the immobilized enzyme reactor and the ordinate represents the DPPH radical scavenging rate (%).
[0104] according to Figure 5It can be seen that the enzymatic hydrolysis efficiency of s-MOF@E reactor is generally lower than that of h-MOF@E reactor, which may be related to the relatively low enzyme loading of s-MOF@E. Snake skin collagen has the best enzymatic hydrolysis effect by h-MOF@E1, with a hydrolysis degree of 46.21% and a DPPH radical scavenging rate of 38.12%, which is significantly higher than other immobilized enzyme reactors. When the carrier remains unchanged, the hydrolysis degree and DPPH radical scavenging rate of the four proteases are E1 (trypsin) > E4 (flavor protease) > E3 (pepsin) > E2 (papain) from large to small. This shows that the type of carrier and enzyme will affect the activity of the immobilized enzyme.
[0105] (3) Optimization of enzymatic hydrolysis conditions of h-MOF@E1
[0106] Accurately weigh 25 mL of the snake skin collagen solution obtained in (1), add 3 mg of h-MOF@E1 from Example 1 to obtain a reaction solution, adjust the pH of the reaction solution to 7.0, and then heat it to 50°C with a constant temperature magnetic stirrer. Perform enzymatic hydrolysis for 3 hours, and measure the degree of hydrolysis and DPPH radical scavenging rate of the enzymatic solution. The amount of h-MOF@E1 added was set to 1 mg, 2 mg, 3 mg, 4 mg and 5 mg; the pH of the reaction solution was 5, 6, 7, 8 and 9; the heating temperature was 40°C, 45°C, 50°C, 55°C and 60°C; and the enzymatic hydrolysis reaction time was 2h, 3h, 4h, 5h and 6h. The effects of different h-MOF@E1 addition amounts, pH values, temperatures and enzymatic hydrolysis times on the activity of the immobilized enzyme were investigated by controlling the single variable method. The results are as follows: Figure 6 As shown, Figure a shows the hydrolysis rate and DPPH radical scavenging rate of the enzymatic hydrolysate with different enzyme addition amounts, in which the abscissa in the figure represents the enzyme addition amount, the left ordinate represents the hydrolysis rate (%), and the right ordinate represents the DPPH radical scavenging rate (%), Figure b shows the hydrolysis rate and DPPH radical scavenging rate of the enzymatic hydrolysate with different pH values, in which the abscissa in the figure represents the pH value, the left ordinate represents the hydrolysis rate (%), and the right ordinate represents the DPPH radical scavenging rate (%), Figure c shows the hydrolysis rate and DPPH radical scavenging rate of the enzymatic hydrolysate with different temperatures, in which the abscissa in the figure represents the temperature, the left ordinate represents the hydrolysis rate (%), and the right ordinate represents the DPPH radical scavenging rate (%), Figure d shows the hydrolysis rate and DPPH radical scavenging rate of the enzymatic hydrolysate at different times, in which the abscissa in the figure represents the time, the left ordinate represents the hydrolysis rate (%), and the right ordinate represents the DPPH radical scavenging rate (%).
[0107] according to Figure 6It can be seen that with the increase of h-MOF@E1 addition, the hydrolysis rate and free radical scavenging rate of the enzymatic solution both show an upward trend. Due to the initial increase in the amount of immobilized enzyme added, the substrate collagen was fully hydrolyzed and the hydrolysis rate increased. When the addition amount reached 4 mg, the hydrolysis rate and free radical scavenging rate both tended to be flat. Due to the insufficient substrate collagen, the enzyme dosage reached an oversaturated state. Therefore, considering the economic cost, 4 mg was selected as the optimal immobilized enzyme addition amount; when the pH value was between 5.0 and 8.0, the hydrolysis rate and free radical scavenging rate both showed an upward trend; when the pH value was 8.0, the hydrolysis rate and free radical scavenging rate both reached the maximum; when the pH value>8.0, the hydrolysis rate and free radical scavenging rate both gradually decreased. Since the spatial configuration of the protease will change due to the influence of pH value, the protease activity will decrease or even be inactivated when the pH value is not suitable, and the dissociation state of the substrate and the protease will also be affected by the pH value, thereby affecting the hydrolysis rate of the protein. When the pH value is 8.0, the enzymatic activity of the immobilized enzyme is the strongest and the enzymatic hydrolysis effect is the best; when the enzymatic hydrolysis temperature is between 40 and 50°C, the hydrolysis rate and the free radical scavenging rate gradually increase; when the enzymatic hydrolysis temperature is 50°C, the hydrolysis degree and the free radical scavenging rate both reach the maximum; when the enzymatic hydrolysis temperature is greater than 50°C, the hydrolysis degree and the free radical scavenging rate both show a downward trend. Therefore, the optimal temperature for immobilized enzyme hydrolysis is 50°C; when the enzymatic hydrolysis time is between 2 and 4h, the hydrolysis rate and the free radical scavenging rate both show an upward trend, and the enzymatic hydrolysis reaction is in the accelerated reaction stage; when the enzymatic hydrolysis time is 4h, the hydrolysis degree and the free radical scavenging rate both reach the maximum. As the enzymatic hydrolysis time increases, the substrate concentration decreases accordingly, and the concentration of the generated complex increases, which covers the active center of the protease and inhibits the enzymatic reaction, resulting in a decrease in the degree of collagen hydrolysis. Therefore, the optimal enzymatic hydrolysis conditions for the h-MOF@E1 reactor were finally determined to be 4 mg of immobilized enzyme reactor addition, 50 °C enzymatic hydrolysis temperature, 8.0 enzymatic hydrolysis pH, and 4 h enzymatic hydrolysis time.
[0108] Test Example 3: Study on the recycling performance of h-MOF@E1
[0109] Recyclability is another important indicator for measuring the performance of immobilized enzymes. Accurately weigh 25 mL of the snakeskin collagen solution in Experimental Example 2, add 4 mg of h-MOF@E1 in Example 1 to obtain a reaction solution, adjust the pH of the reaction solution to 8.0, and then heat it to 50°C with a constant temperature magnetic stirrer. Perform the enzymatic hydrolysis reaction for 4 hours, determine the degree of hydrolysis and DPPH radical scavenging rate of the enzymatic hydrolyzate, and perform 20 cycles to study the recycling performance of h-MOF@E1. The effect of different cycle times of the h-MOF@E1 reactor on the enzymatic hydrolysis efficiency of the immobilized enzyme was studied. The results are as follows: Figure 7 As shown in the figure, the horizontal axis represents the cycle (number), and the vertical axis represents the enzymatic efficiency (%).
[0110] according to Figure 7It can be seen that when the h-MOF@E1 reactor was recycled 20 times under the optimal enzymatic hydrolysis conditions, the hydrolysis rate and free radical scavenging rate of the enzymatic hydrolyzate added with the h-MOF@E1 reactor did not decrease significantly, indicating that the h-MOF@E1 reactor has good reuse performance and good commercial prospects.
[0111] As can be seen from the above embodiments, the present invention provides a preparation method and application of an h-MOF@E immobilized enzyme reactor. The present invention constructs h-MOF nanospheres with a single-opening hollow morphology through a one-pot solvothermal reaction method. The h-MOF nanospheres are formed by cross-assembly of ultrathin nanosheets with a thickness of 1 to 2 nm, have a large specific surface area, and also contain a large irregular break with a pore size of about 100 to 500 nm. The large specific surface area and irregular break structure of the h-MOF nanospheres are conducive to increasing the enzyme immobilization capacity. At the same time, the large internal cavity will not form physical extrusion on the active enzyme, affect the enzyme as a flexible molecule, and affect its performance. Using h-MOF nanospheres as carriers, a novel single-opening hollow spherical h-MOF@E immobilized enzyme reactor can be prepared by a simple immobilization technology. The obtained h-MOF@E immobilized enzyme reactor has excellent snakeskin collagen catalytic activity and reusability, and has potential commercial value.
[0112] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a h-MOF@E immobilized enzyme reactor, characterized in that: The steps include: (1) mixing terephthalic acid, N,N-dimethylacetamide and isopropyl alcohol to obtain a mixed solution A; (2) mixing nickel acetate tetrahydrate, zinc acetate dihydrate, N,N-dimethylacetamide and isopropanol to obtain a mixed solution B; (3) mixing the mixed solution A with the mixed solution B, heating for 2 to 4 hours, centrifuging, washing, and drying to obtain h-MOF nanospheres; (4) mixing the h-MOF nanospheres with the active protease solution, shaking for 2 to 4 hours, centrifuging, washing, and drying to obtain the h-MOF@E immobilized enzyme reactor; The mass volume ratio of terephthalic acid and N,N-dimethylacetamide in step (1) is 16-20 mg: 6-8 mL; The mass volume ratio of the terephthalic acid and isopropyl alcohol is 16-20 mg: 3-5 mL.
2. The preparation method according to claim 1, characterized in that: The mass ratio of nickel acetate tetrahydrate to zinc acetate dihydrate in step (2) is 48-50:21-22; The mass volume ratio of the nickel acetate tetrahydrate and N,N-dimethylacetamide is 48-50 mg: 6-8 mL; The mass volume ratio of the nickel acetate tetrahydrate and isopropanol is 48-50 mg:3-5 mL.
3. The preparation method according to claim 1, characterized in that: The volume ratio of the mixed solution A to the mixed solution B in step (3) is 1-2:1-2.
4. The preparation method according to claim 1, characterized in that: The heating temperature in step (3) is 140-160°C.
5. The preparation method according to claim 1, characterized in that: The mass volume ratio of the h-MOF nanospheres and the active protease solution mixed in step (4) is 1-2 mg: 1-2 mL.
6. The preparation method according to claim 1, characterized in that: The active protease in step (4) is trypsin, papain, pepsin or flavor protease; The initial concentration of the active protease solution is 0.5-1.5 mg / mL.
7. The preparation method according to claim 1, characterized in that: The oscillation speed in step (4) is 100-200 rpm.
8. The h-MOF@E immobilized enzyme reactor obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The structure of the h-MOF@E immobilized enzyme reactor is a single-opening hollow sphere.
9. Use of the h-MOF@E immobilized enzyme reactor obtained by the preparation method according to any one of claims 1 to 7 in the preparation of antioxidant, anti-aging or anti-cancer products.